A Periodic Event-Triggered Design of Robust Filtering for T-S Fuzzy Discrete-Time Systems - Zhang, Zuchang; Lin, Dongliang; Wang, Xingyi; Shao, Zhenhua; Lin, Wenzhong (Frontiers in Neuroscience, 2019)
Periodic event-triggered control (PETC) is a control strategy consisting of event-triggered control (ETC) and conventional periodic sampled-data control. By using event-triggering mechanisms (ETM) to verify periodically whether or not to transmit and to compute the measured output, communication and computational datum are significantly reduced while still retaining a satisfactory performance. This paper investigates the PETC shceme of robust H∞ filtering for a class of uncertain discrete-time Takagi-Sugeno (T-S) fuzzy systems, where the sample time is assumed to be a constant. To analyze the filtering problems of the PETC strategy, we present two frameworks based on perturbed linear and piecewise linear systems to model the filtering error systems. Sufficient conditions for the existence of robust H∞ filter are derived under these two frameworks, respectively, and the filter gains can be obtained by solving a set of linear matrix inequalities (LMIs). Finally, a simulation example is provided to illustrate the effectiveness of the proposed approach.